Real-time biomolecular simulations: - Peters, Michael H. (McGraw Hill, 2007)
Real-Time Biomolecular Simulations provides you with proven strategies for shortening the time between product research, breakthrough, and introduction into the market. Based on the author's own innovative research, this rigorous, groundbreaking guide demonstrates how the simulation process can be accelerated yet still provide accurate, dependable results.